Public-Private-Partnership for Effective Delivery of Technical Vocational Education in Enhancing Graduate Employability Skills During The Era of Covid-19 Pandemic in Nigeria - Oladiran Stephen Olabiyi; Gideon O Adedayo; Akinseyi Ipinlaye; Sunday Odunayo Okeowo (Faculty of Engineering, Universitas Negeri Yogyakarta, 2022)
The study investigates public-private partnerships for enhancing TVE delivery towards graduate employability skills during COVID-19. A survey research design was employed. Three research questions and three null hypotheses, tested. Significance level of 05%, the respondents consisted of 139 human resources managers and TVE lecturers. Data was obtained using a structured questionnaire. The reliability coefficient of the instrument yields α = .76, Using Cronbach Alpha. Mean and standard deviation was used to answer research questions, independent sample t-test was employed to test null hypotheses. Findings revealed: Training resources such as an online library, interactive multimedia, digital textbooks and internet connectivity are essentials. No significant difference in the mean responses of respondents regarding the private sector's innovative roles in improving training resources in enhancing effective TVE delivery towards developing graduates employability skills during and post COVID-19. It was recommended that private sectors should be involved in the training of TVE graduates by identifying demand for skills, feeding into curricula development, monitoring and evaluation activities; TVE lecturers should offer quality and effective teaching and learning that will facilitate and promote employability skills.